2020
DOI: 10.1103/physrevresearch.2.013335
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in twisted transition-metal dichalcogenide bilayers: Ultrasoft phasons and a transition from a superlubric to a pinned phase

Abstract: The tunability of the interlayer coupling by twisting one layer with respect to another layer of two-dimensional materials provides a unique way to manipulate the phonons and related properties. We refer to this engineering of phononic properties as twistnonics. We study the effects of twisting on low-frequency shear modes (SMs) and layer breathing modes in a transition-metal dichalcogenide (TMD) bilayer using atomistic classical simulations. We show that these low-frequency modes are extremely sensitive to tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 69 publications
(92 reference statements)
4
57
0
Order By: Relevance
“…The range here is from several tens to one hundred nanometers [33]. The domain formation was first predicted in [36], and confirmed by density functional theory calculations [33,34,37,38], and by a classical modelling [31]. Interestingly, in atomically-reconstructed structures the domain periodicity depends in the same way on the twist-angle deviation, as the moiré periodicity in structures, where the twist angle is larger than the critical value for atomic reconstruction [37].…”
Section: Introductionsupporting
confidence: 62%
“…The range here is from several tens to one hundred nanometers [33]. The domain formation was first predicted in [36], and confirmed by density functional theory calculations [33,34,37,38], and by a classical modelling [31]. Interestingly, in atomically-reconstructed structures the domain periodicity depends in the same way on the twist-angle deviation, as the moiré periodicity in structures, where the twist angle is larger than the critical value for atomic reconstruction [37].…”
Section: Introductionsupporting
confidence: 62%
“…27 via conformational considerations, and indeed, density functional theory calculations confirmed that in the above cases, the two stacking configurations are the energetically favorable lattice arrangements 24,25,28,29 (also see Ref. 30 for a classical modeling). For R-type stacking, two energetically degenerate commensurate configurations are possible for a heterobilayer [see Fig.…”
mentioning
confidence: 65%
“…If it's possible to tune to such a large J 2 /J 1 ratio, it would allow to explore the interplay between the moiré scale incommensurate magnetic structure, and its gapless phason modes, with the atomic scale incommensurate lattice structure, and its gapless phonon modes. 67,68 For smaller ratios of J 2 /J 1 0.3, the 120 • order is stabilized. For φ = π/6 it is particularly stable, and has a fixed chirality, which leaves only a single BKT transition at finite temperature, with an expected T BKT J 1 .…”
Section: Discussionmentioning
confidence: 99%